The role of neuronal activity in regulating metabolism in mouse and human astrocytes. (23rd February 2017) - Jiwaji, Zoeb; Hasel, Philip; Chandran, Siddharthan; Hardingham, Giles
Abstract: Background: The CNS has high energy requirements and CNS metabolism is often disrupted in disease. Astrocytes, the predominant CNS glucose utilisers, convert glucose to lactate to fuel neuronal metabolism. However, the extent to which this pathway is regulated by neuronal activity is poorly understood. We hypothesised that neuronal activity increases astrocytic metabolism, and have investigated the signalling underlying neuron–astrocyte metabolic crosstalk in mouse and human systems. Methods: Primary mouse or human stem-cell derived astrocytes, expressing fluorescence-resonance energy transfer (FRET) biosensors for glucose or lactate, were co-cultured in vitro with primary cortical neurons. Neuronal activity was altered with 24 h of bicuculline (high activity) or tetrodotoxin (low activity). Glucose and lactate flux were determined by the rate of change of FRET ratio after inhibition of glucose uptake or lactate export. Transcriptomic analysis was done by RNA sequencing. Findings: Neuronal activity increased glucose metabolism in mouse astrocytes (rate of change in FRET ratio: bicuculline mean 1·58 per s [SD 0·17] vs tetrodotoxin 0·620 [0·20], p<0·0001) and human astrocytes (1·30 [0·32] vs 0·775 [0·19], p<0·0001). Neuronal activity also increased lactate production in mouse astrocytes (0·572 [0·38] vs 0·281 [0·21], p=0·028). Metabolic changes persisted after transfer from high to low activity conditions. Transcriptome analysis found activity-dependent upregulation of major components of the astrocyte–neuron lactate shuttle, with enrichment for the cAMP response element (CREB) promoter motif. CREB inhibition reversed activity-induced effects, and constitutively-active CREB was sufficient to increase astrocyte metabolism in low-activity conditions. Interpretation: Our study found that neuronal activity, in mouse and human astrocytes, drove expression of metabolic genes and led to long-lasting enhancement of pathways for astrocyte–neuron metabolic support. These activity-dependent changes occured via activation of the CREB signalling pathway. These findings could have consequences for CNS metabolism when neuronal activity is reduced after neurodegeneration or iatrogenically during prolonged anaesthesia or sedation. Funding: Wellcome Trust.